Hydroxyapatite Nanoparticles Facilitate Osteoblast Differentiation and Bone Formation Within Sagittal Suture During Expansion in Rats - Liang W; Ding P; Li G; Lu E; Zhao Z (Dove Medical Press, 2021)
Wei Liang, Pengbing Ding, Guan Li, Enhang Lu, Zhenmin Zhao Department of Plastic Surgery, Peking University Third Hospital, Beijing, 100191, People’s Republic of ChinaCorrespondence: Zhenmin ZhaoDepartment of Plastic Surgery, Peking University Third Hospital, Beijing, 100191, People’s Republic of ChinaEmail zzmbysy@sina.comBackground: The potential of relapse of craniofacial disharmony after trans-sutural distraction osteogenesis is high due to the failure to produce a stable bone bridge in the suture gap. The aim of this study is to evaluate whether hydroxyapatite nanoparticles (nHAP) have the effect of promoting osteoblast differentiation of suture-derived stem cells (SuSCs) and bone formation in sagittal suture during expansion.Methods: SuSCs were isolated from sagittal sutures and exposed to various concentrations of nHAP (0, 25, 50, and 100 μg mL− 1) to determine the optimal concentration of nHAP in osteoblast differentiation via performing Western Blotting and RT-qPCR. Twenty 4-week-old male Sprague–Dawley rats were randomly assigned into 4 groups: SHAM (sham-surgery), distraction, ACS (absorbable collagen sponge) and ACS+nHAP groups. In the ACS and ACS+nHAP groups, saline solution and nHAP suspended in a saline solution were delivered by ACS placed across the sagittal suture, respectively. In the latter three groups, the suture was expanded for 14 days by 50 g of constant force via a W shape expansion device. Suture gap area, bone volume fraction (BV/TV) and bone mineral density (BMD) of sagittal sutures were assessed via micro-CT, while the mechanical properties of sagittal sutures were evaluated via nanoindentation test. The efficacy of nHAP on bone formation in sagittal suture was also evaluated via BMP-2 immunohistochemistry staining.Results: The expression of osteoblast related genes and proteins induced by 25μg mL− 1 nHAP were significantly higher than the other groups in vitro (p< 0.05). Furthermore, treating with 25μg mL− 1 nHAP in vivo, the suture gap area was significantly reduced when compared with the distraction group. Correspondingly, the BV/TV, BMD, hardness and modulus of sagittal sutures were significantly increased in the ACS+nHAP group (p< 0.05).Conclusion: The 25μg mL− 1 dose of nHAP delivered by ACS can facilitate bone formation into the sagittal suture during expansion via inducing osteoblast differentiation of SuSCs.Keywords: hydroxyapatite nanoparticles, suture-derived stem cells, osteoblast differentiation, sagittal suture, bone formation